2018
DOI: 10.3390/ijms19113670
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Keratin as Nanotechnology-Based Drug Delivery System for the Pharmacological Treatment of Osteosarcoma

Abstract: Osteosarcoma therapy might be moving toward nanotechnology-based drug delivery systems to reduce the cytotoxicity of antineoplastic drugs and improve their pharmacokinetics. In this paper, we present, for the first time, an extensive chemical and in vitro characterization of dual-loaded photo- and chemo-active keratin nanoparticles as a novel drug delivery system to treat osteosarcoma. The nanoparticles are prepared from high molecular weight and hydrosoluble keratin, suitably functionalized with the photosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 50 publications
2
33
0
1
Order By: Relevance
“…Kusuzaki et al showed that AO-PDT has a strong cytocidal effect, not only on chemosensitive mouse OS cells, but also on MDR mouse OS cells [157]. This effects on MDR were confirmed by Martella et al [158] in vitro study demonstrating that the combination of PTX-Ce6@Ker (paclitaxel loaded in keratine nanoparticles functionalized with the photosensitizer Chlorin-e6) and PDT was highly effective on MDR Saos2 cells. A recent interesting application of PDT is its combination with doxorubicin engineered osteogenic scaffold that would allow to act simultaneously destroying the tumor by increasing the temperature and the release of doxorubicin (after laser stimulation), and promoting bone regeneration thanks to the osteoinductive characteristics of the scaffold [159,160].…”
Section: Application Of Biophysical Therapies In Osteosarcomamentioning
confidence: 92%
“…Kusuzaki et al showed that AO-PDT has a strong cytocidal effect, not only on chemosensitive mouse OS cells, but also on MDR mouse OS cells [157]. This effects on MDR were confirmed by Martella et al [158] in vitro study demonstrating that the combination of PTX-Ce6@Ker (paclitaxel loaded in keratine nanoparticles functionalized with the photosensitizer Chlorin-e6) and PDT was highly effective on MDR Saos2 cells. A recent interesting application of PDT is its combination with doxorubicin engineered osteogenic scaffold that would allow to act simultaneously destroying the tumor by increasing the temperature and the release of doxorubicin (after laser stimulation), and promoting bone regeneration thanks to the osteoinductive characteristics of the scaffold [159,160].…”
Section: Application Of Biophysical Therapies In Osteosarcomamentioning
confidence: 92%
“…Due to its exquisite and versatile loading capacity, keratin has also been harnessed to create bimodal nanoformulations that combine chemotherapeutics and photodynamic therapy. Martella et al functionalized high molecular weight keratin with the photosensitizer Chlorin-e6 (Ce6) and induced spontaneous nanoparticle formation by mixing the protein with paclitaxel, a chemotherapeutic that aggregates with the hydrophobic residues in keratin [ 108 ]. This is an attractive bottom-up nanoparticle fabrication strategy, as it did not require any toxic crosslinkers or downstream purification steps for nanoparticle fabrication.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…Although Ce6 typically experiences a drop in fluorescence in acidic conditions, the keratin protected the photosensitizer and no decrease in fluorescence was observed. Further, the nanoparticle formulation transported the paclitaxel in a three-dimensional tumor model system without reducing the drug's potency [ 108 ]. Keratin nanoparticles have also been engineered for mucoadhesive drug delivery.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…3 Among numerous antitumor agents, taxanes is widely applied for treating breast and pancreatic cancers, and the efficacy of taxanes for treating OS was previously revealed to be a great success in high-grade OS and recurrent or metastatic soft-tissue sarcomas. 4 However, increasing chemoresistance was saw in a great number of OS patients in the past few years, therefore the study of the underlying mechanisms regarding the chemosensitivity of OS cells is of great importance to enhance the survival rate. 5 The dysregulation of microRNAs (miRNAs), small noncoding RNAs, have been observed in many human pathologies, and most prominently, in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%